The necessity or not of the addition of fusion to decompression for lumbar degenerative spondylolisthesis patients: A PRISMA compliant meta-analysis - Wu, Jun; Zhang, Jingwei; Xu, Ting; Pan, Yongli; Cui, Baolong; Wei, Wei; Gao, Yunlong; Yu, Haiguang; Huang, Qingliang; Long, Xin-quan; Zhou, Yu-fan (Medicine (Baltimore), 2021)
The new emerging application of decompression combined with fusion comes with a concern of cost performance, however, it is a lack of big data support. We aimed to evaluate the necessity or not of the addition of fusion for decompression in patients with lumbar degenerative spondylolisthesis. Potential studies were selected from PubMed, Web of Science, and Cochrane Library, and gray relevant studies were manually searched. We set the searching time spanning from the creating date of electronic engines to August 2020. STATA version 11.0 was exerted to process the pooled data. Six RCTs were included in this study. A total of 650 patients were divided into 275 in the decompression group and 375 in the fusion group. No statistic differences were found in the visual analog scales (VAS) score for low back pain (weighted mean difference [WMD], -0.045; 95% confidence interval [CI], -1.259-1.169; P = .942) and leg pain (WMD, 0.075; 95% CI, -1.201-1.35; P = .908), Oswestry Disability Index (ODI) score (WMD, 1.489; 95% CI, -7.232-10.211; P = .738), European Quality of Life-5 Dimensions (EQ-5D) score (WMD, 0.03; 95% CI, -0.05-0.12; P = .43), Odom classification (OR, 0.353; 95% CI 0.113-1.099; P = .072), postoperative complications (OR, 0.437; 95% CI, 0.065-2.949; P = .395), secondary operation (OR, 2.541; 95% CI 0.897-7.198; P = .079), and postoperative degenerative spondylolisthesis (OR = 8.59, P = .27). Subgroup analysis of VAS score on low back pain (OR = 0.77, 95% CI, 0.36-1.65; P = .50) was demonstrated as no significant difference as well. The overall efficacy of the decompression combined with fusion is not revealed to be superior to decompression alone. At the same time, more evidence-based performance is needed to supplement this opinion.